PATOGENESIS PENYAKIT KOLERA PADA MANUSIA - Musjaya M. Guli (Biology Department, Mathematics and natural science, Tadulako University, 2016)
Vibrio cholerae is the causative agent of cholera is characterized by continuous diarrhea in patients. V.cholerae strains that have ctx genes that can produce cholera toxin (cholera toxin = CT), which is a toxigenic strain. The toxigenic strain responsible for an outbreak of cholera. Pathogenic V. cholerae is due to two main factors, namely cholera toxin (CT) and TCP pili (toxin coregulatedpilus), which is responsible for the ability of V. cholerae attaches to epithelial cells intestinal. The mechanism of bacterial infection generally consists of 2 phases, the first phase of bacterial will latch preceded by pili to host cells that are anchoring, after that proceed with sticking through the outer membrane cell attachment is doching. After the invasion and colonization, V. cholerae which will remove pathogens and toxin coregulated CT philus (TCP). Type IV pili are found in V. cholerae are important in the formation of colonies, biofilms, and adhesion and secretion of proteins in the outer membrane. V. cholerae can invade macrophage phagocytosis surrounded by a membrane that V. cholerae can damage the membrane and spread into the cytoplasm. Keywords: Cholera, Pathogenicity, Cholera toxin (CT), toxin coregulatedpilus (TCP), Vibrio cholerae